A Study on an Unpressurized Medium-Temperature-Differential Stirling Engine Integrated with a New Spiral-Patterned Flat-Flame Burner and a New Spiral-Finned Hot-End Plate. (15th February 2023) - Chen, Wen-Lih; Currao, Gaetano M. D.; Wu, Chih-Yung; Evan, Bah; Mao, Chieh-Yu; Tsai, Shu-Wei; Yu, Chih-Yuan
Abstract : The present study experimentally investigates the performance of a power generator constituted by an unpressurized Stirling engine coupled with a new flat-flame burner. The operative temperature differential of the Stirling engine is within the medium range (around 400 K or less). In this work, there are two types of the engine's hot-end-plate designs, a conventional flat plate and the new type with spiral fins developed within this framework. Consequently, the new hot-end-plate design forms spiral-patterned channels to enhance the engine's heat input rate, thus partly compensating for the inherently low thermal efficiency of an unpressurized engine. The spiral fins are used to increase the resident time of the flue gas and increase the heat-transfer area. In addition, engine performance is measured for two types of fuels, namely, DME (renewable) and propane (fossil). Using propane, the new hot-end plate allows for a maximum electric power output of 24.6 W, which is typically superior to common unpressurized Stirling engines. Compared to the conventional hot-end plate, the new hot-end plate improved electric power output and the thermal-to-electric efficiency up to 63% and 47%, respectively. The study also proved the effectiveness of applying the integration of the new hot-end plate and the new flat-flame burner on boosting the power output of the present Stirling engine generator.